Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/bes2.1447
|View full text |Cite
|
Sign up to set email alerts
|

Limited Ecosystem Recovery from Simulated Chronic Nitrogen Deposition

Abstract: The realization that anthropogenic nitrogen (N) deposition is causing significant environmental change in many ecosystems has led to lower emissions of reactive N and deposition rates in many regions. However, the impacts of N deposition on terrestrial ecosystems can be long lasting, with significant inertia in the return of the biota and biogeochemical processes to baseline levels. To better understand patterns of recovery and the factors that may contribute to slow or no responses following declines in N dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Moreover, N amendment frequency may affect ecosystem recovery rates after amendments cease. For example, following cessation of long‐term N additions, higher frequency inputs (weekly throughout a year) show rapid recovery in soil pH (Power, Green, Barker, Bell, & Ashmore, ), whereas infrequent amendments (three times per year) show persistent negative effects on soil pH (Bowman et al, ). Our study demonstrated that N‐induced effects on soil pH were smaller in the more frequent 12X relative to less frequent 2X‐N amendments (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, N amendment frequency may affect ecosystem recovery rates after amendments cease. For example, following cessation of long‐term N additions, higher frequency inputs (weekly throughout a year) show rapid recovery in soil pH (Power, Green, Barker, Bell, & Ashmore, ), whereas infrequent amendments (three times per year) show persistent negative effects on soil pH (Bowman et al, ). Our study demonstrated that N‐induced effects on soil pH were smaller in the more frequent 12X relative to less frequent 2X‐N amendments (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…, Bowman et al. ), so the availability of food to fungivorous micro‐arthropods would have to be tested directly. Second, an increase in the abundance of predators could have controlled Collembola abundance.…”
Section: Discussionmentioning
confidence: 99%
“…If this effect was reduced shortly after cessation of the treatments, there may not have been sufficient food available to sustain high Collembola abundances. However, the effects of nitrogen addition are reported to be long-lasting and recovery is often incomplete (Street et al 2015, Bowman et al 2018, so the availability of food to fungivorous micro-arthropods would have to be tested directly. Second, an increase in the abundance of predators could have controlled Collembola abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Other constituents relevant to the NADP network include acid anions and base cations. The dissolution of calcium carbonate and other dust minerals either in precipitation or in depositional water bodies can provide readily available Ca 2+ and acid neutralizing capacity (ANC) to remote mountain lakes and soils 1,38,40,[57][58][59][60][61] . For regions with catchments having low natural calcium abundances, this contribution may be a critical source of calcium to aquatic organisms with relatively high calcium requirements, e.g., Daphnia.…”
Section: Discussionmentioning
confidence: 99%